THE IMPLEMENTATION OF CODE SWITCHING FOR MIXED-ABILITY ESP CLASSES - Maulida Yuniswati (DIDAKTIKA, 2015)
Code switching is the alternation between two or more languages in a speaker's speech(Yamat et.al, 2011:19). It is believed that code switching occurs naturally as an indicator ofbilingualism. Classroom code switching starts to gain importance in language learningclasses (Chowdhury, 2013:42) and becomes a controversial issue in the EFL classes. Thelanguage teachers who support classroom code switching in the EFL classes consider that itfacilitates the continuity of the speech. It also serves as an aid to transfer meaning andcommunicative purpose. On the other hand, the ones who against the application of codeswitching in classrooms view a mother tongue as interference which hampers the learningenvironment. It makes the students become less interested in listening to the targetlanguage and gain low English proficiency. However, from several notable papers underclassroom code switching, it can be concluded that code switching as one of scaffoldingactivities does assist the students in learning English. Code switching plays an importantrole both as the facilitative and the affective function.